Advanced Technologies of Quantum Key Distribution - Gnatyuk, Sergiy (IntechOpen, 2018)
This book explores both the state of the art and the latest developments in QKD. It describes the fundamental concepts and practical aspects of QKD from a viewpoint of information security and quantum channel efficiency improvement. The purpose of this book is to extend and update the knowledge of the readers in the dynamically changing field of QKD. The authors attempt to present in detail their results of scientific research, which is divided into two sections - Modern QKD Technologies and Quantum Channel Construction. It will be useful for researchers, engineers, graduates, and doctoral students working in quantum cryptography and information security-related areas.